Integrated Operating Scenario to Achieve 100-Second, High Electron Temperature Discharge on EAST - 钱金平 龚先祖 万宝年 刘甫坤 王茂 徐【日山】东 胡纯栋 王亮 李二众 曾龙 提昂 沈飚 林士耀 邵林明 臧庆 刘海庆 张斌 孙有文 徐国盛 梁云峰 肖炳甲 胡立群 李建刚 (Plasma science & technology, 2016)
Stationary long pulse plasma of high electron temperature was produced on EAST for the first time through an integrated control of plasma shape, divertor heat flux, particle exhaust, wall conditioning, impurity management, and the coupling of multiple heating and current drive power. A discharge with a lower single null divertor configuration was maintained for 103 s at a plasma current of 0.4 MA, q95 ≈7.0, a peak electron temperature of 〉4.5 keV, and a central density ne（0）-2.5×10^19 m^-3. The plasma current was nearly non-inductive （Vloop 〈0.05 V, poloidal beta - 0.9） driven by a combination of 0.6 MW lower hybrid wave at 2.45 GHz, 1.4 MW lower hybrid wave at 4.6 GHz, 0.5 MW electron cyclotron heating at 140 GHz, and 0.4 MW modulated neutral deuterium beam injected at 60 kV. This progress demonstrated strong synergy of electron cyclotron and lower hybrid electron heating, current drive, and energy confinement of stationary plasma on EAST. It further introduced an example of integrated ＂hybrid＂ operating scenario of interest to ITER and CFETR.